(3GdOQ GdfajSs - (3CHh SYjO SfLQ Hf YHO Gddg GdfGUQi YQa HGdLGhdis; (3CHh YHO Gddg eMeO Hf EOQjS Hf GdYHGS Hf YKeGf Hf TGaY (B( (3GdEeGe GdTGaYj (B)(3,J (B204 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdcHjQ GdeJYGd Pi GdYXeI hGdLdGd hHYO aEfg deG ef Gddg Ydi eeG ef Hg ef JQJjH eSfO GdGeGe GdCYXe CHj YHO Gddg eMeO Hf EOQjS GdTGaYi GdeWdHi s
(3BNQgG (B:s
(3heJi CaGb hGMOkG ef ghdGA Ch XgQJ MGFV ai hbJ GdUdGI aYdjgeG Cf fUdjG dCfgeG eef Ydjg aQV GdUdGI hGddg CYde gPG fUg ai GdCe ai HGH dGJbVi GdMGFV dUdGI Je s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B26 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B32s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1683s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdMOjK h GdeUWdMs